Manfaat Body Mekanik dan Hamstring Exercise terhadap Pengurangan Nyeri Pinggang Ibu Hamil Trimester III - Puspitasari, Lina; Ernawati, Ernawati (Jurnal Kebidanan Harapan Ibu Pekalongan, 2020)
Background. Low back pain is the pain in the lower back region that occurs in 50% of pregnant women and it can be overcome with training. Mechanical Body is an effort to facilitate muscle movement without causing muscle tension so as to reduce musculoskeletal injury. Hamstring exercise action can also support the reduction of low back pain, this is caused by the exercise process in the form of a reduction that results in muscle flexion resulting in reduced muscular injury and an increase in body metabolism. The purpose of this study was to determine the benefits of body mechanics and hamstring exercise on the reduction of low back pain in third trimester pregnant women. Research methods. This study uses a comparative test analysis type approach. Subjects in this study were 36 third trimester pregnant women who experienced complaints of low back pain. This research was conducted at PMB Midwife Utami, Amd.Keb. The study was conducted in November 2018-March 2019. This study used the Wilcoxon Signed Rank test in the SPSS 20 software program. The results of this study used the Wilcoxon Signed Rank formula. Based on the calculation results using a computerized analysis of the results obtained Z value of - 5.255 and p value (Asymp Sign 2 tailed) of 0,000 where the value is below the critical limit of research or a point of significance of 0.05 (5%) and Z table value of 1.68830. The conclusion of this study is that there are benefits of mechanical body and hamstring exercise on the reduction of low back pain in third trimester pregnant women.